I do it better: How social and emotional learning environment enhances Assessment for Learning strategies in science classrooms - Sathasivam, R.V.; Abdul Rahim, S.S. (2017)
This paper describes part of a larger national scale study on Malaysian teachers' classroom practices in terms of pedagogical, curriculum implementation and assessment. The original study involved 153 Year 7 teachers from 24 randomly selected schools. The data was obtained from a questionnaire and video recordings of three lessons for each teacher. In the context of teachers' classroom assessment practices, the data was analysed using a self-developed Assessment for Learning (AfL) rubric that contained tour- level performance rating. The findings of teachers' AfL practices revealed that a large majority of teachers' practices were at the lowest level and were deemed unsatisfactory. The present study was inspired by these findings. The present study used a qualitative approach where two teachers were purposely selected based on their AfL practices. The study investigated how these teachers created (if any) social and emotional learning environments and to see how these environments affected the AfL strategies the teachers implemented. Using the video recordings of the three lessons and transcribing the classroom discourses, the data was analysed by identifying 'episodes' that focused on student·teacher interactions during the implementation of AfL strategies. Our findings revealed that one teacher was able to create a more social and emotional learning environment and this led to active participation of her students and them taking responsibility for their own learning. The research findings may have implications on how teacher education and teacher development programmes could incorporate elements of how to create social and emotional learning environments to improve teachers' AfL skills.